Profile of street children in carrying out singing activities while learning - Deni Wepriadi (Education and Social Sciences Review, 2021)
This research is motivated by a street child who conducts learning activities on the sidelines of his work as a busker. This study aims to describe the picture of: the purpose of busking activities while learning, busking time while learning, the media used in busking while learning, the methods used in busking while learning, the response of the busking environment while learning and the future hopes of busking while learning as a street child. This research uses a qualitative approach with a type of case study. The subject of the research is a street child who does busking while learning. Information is captured by the snowball technique. Data collection is done through participatory observation and interviews. Data analysis is done by selecting data, compiling data into appropriate variables, and writing narratives. It was found that the purpose of his study was clearly stated, namely to continue his education at a higher level in the midst of the economic conditions of his parents who were so difficult and lacking, the time spent doing busking while learning did not interfere with their study time at school or when they were studying in the Imam Bonjol Padang Green Field, learning media used in completing homework assignments given by the teacher at a carton of used mineral water used as a base in doing work, while other media, magazines and newspapers which he often uses as reading material to increase his knowledge, methods learning that is used is question and answer, environmental responses to activities that are often carried out subject is very positive, some are positive and some are negative, the subject's hopes are expressed with an attitude that does not want to simply give up on fate and poverty situation